ANALISIS PERAN KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN - Safiih, Abdul Rahman; Abid, Muhamad (Jurnal Ilmiah Publika, 2023)
The of this research is to analyze "The Role of Leadership in Improving Employee Performance at PT Plasindo Elok in West Jakarta". The research method used is qualitative research. The data collection techniques used were interviews, observations, focus group discussions (FGD) and documentation. The data analysis used in this research is SWOT Analysis. The output of this research is targeted to produce a journal with ISSN on a national scale. The results of the research can be concluded that it can be said to be good, because leaders and employees can overcome all difficulties, obstacles and challenges together. Apart from that, the leadership role can provide an example and motivate each employee to improve their performance in carrying out their duties and activities in order to achieve company goals and success. The performance of employees at PT Plasindo Elok in West Jakarta is quite good, even though there are a few individual problems the employees still provide the best loyalty to the company.